EKSPRESI IFN-γ PADA ILEUM AYAM PETELUR YANG DIVAKSIN AVIAN INFLUENZA DAN DIBERI SUPLEMENTASI PROBIOTIK-CHLORELLA - Retno Wulan Handayani (2007)
The purpose of this study was to find out the expression of IFN-y of ileum's layer which has vaccinated and supplemented with Probiotic-Chlorella. This research used factorial completely random design with six treatments and each treatment repeated seven times. Treatments group consisted of basal protein feed control, low protein feed control, Probiotic supplementation in basal protein feed, Probiotic supplementation in low protein feed, Probiotic-Chlorella supplementation in basal protein feed and Probiotic-Chlorella supplementation in low protein feed. The ileum's layer was collected after twenty four weeks old. The expression of IFN-y was explored by immunohistochemical technique. The data were analyzed by Kruskal –Wallis One – Way Analysis Of Variance By Rank used SPSS for windows 12. The result of this research is supplementation of Probiotic-Chlorella can increase the IFN-y expressions in the lamina propria of ileum 's layer that vaccinated by Avian Influenza.